Molecular determination of the microbial diversity associated with vaginitis and testing their sensitivity to selected antimicrobials - MASSOOMA HILAL HWAIDI AL-ZAIDI; WIJDAN HUSSAIN AL-TAMIMI; AFRODET ABD-ALRAZAQ SALEH (Society for Indonesian Biodiversity, 2023)
Abstract. Al-Zaidi MHH, Al-Tamimi WH, Saleh AAA. 2023. Molecular determination of the microbial diversity associated with vaginitis and testing their sensitivity to selected antimicrobials. Biodiversitas 24: 4253-4261. Millions of women suffer from bacterial vaginitis is associated with several serious health problems. The present study aimed to investigate the microbial diversity and their sensitivity to different antimicrobial agents. Bacterial isolates were identified by genotyping using the 16S rRNA gene sequencing and BLASTn analysis, while conventional mycological methods identified Candida spp. The disc diffusion method was used to study the antimicrobial susceptibility patterns. The molecular identification showed that Escherichia coli (20.8%) and Staphylococcus haemolyticus (20.8%) were the most frequent species, followed by Klebsiella pneumoniae (16.7%). At the same time, Macrococcus caseolyticus, Streptococcus agalactiae, Staphylococcus aureus, and Bacillus cereus were the least prevalent bacteria (4.16%)—all Candida sp. against the selected antimicrobial agents. Thus, molecular assays are important in monitoring microorganisms associated with vaginitis. Prospective genotyping studies are needed to determine these microbes' resistant genes and understand their mode of action and response to drug therapy.